Metode Menghafal dalam Bimbingan Koseling Belajar Sebuah Tinjauan Teoretis - Andri Afriani Andri (Institut Agama Islam (IAI) Nurul Hakim, 2022)
Tutoring with the memorization method is one of the important forms of guidance services held in educational institutions. Memorizing means the activity of keeping in mind intentionally and earnestly. Guidance on learning by way of memorization is more sought at identifying difficulties in memorizing subject matter which includes problems with identification difficulties, recalling, and the ability to use old memories to recognize new ones. The research method that the researcher uses in this journal article is a qualitative descriptive research that is library research which uses books and other literatures as the main object, meaning that in collecting and explaining theoretical studies related to the themes raised in this paper. this journal. Based on the problems in the difficulty of memorizing subject matter to students, this shows that problems that occur in students if not addressed immediately, will greatly affect the acquisition of student achievement. For this reason, things related to the problem of difficulties in memorizing subject matter for students can be found the right solution, in order to avoid bad achievements that will be obtained by students. In line with the duties and roles of the counselor in providing counseling guidance on learning by memorizing.